2017
DOI: 10.1002/j.0022-0337.2017.81.3.tb06273.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Satisfaction with Face‐to‐Face Synchronous Distance Education in a Dental Hygiene Program

Abstract: As universities and colleges seek to reach more students in efficient ways, the use of synchronous distance education (SDE) can be an alternative to traditional classrooms. This study focused on face-to-face SDE, in which classrooms equipped with interactive synchronous technologies allow students in both classrooms and the professor to synchronously see and hear one another. The aims of the study were to aid educators in understanding student concerns, determine whether face-to face SDE was sacrificing overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…One way to increase the quality of students’ education is to familiarize educators with new educational technologies. The qualitative data suggested that technological support and faculty familiarity with E-learning were substantial influences on students’ satisfaction ( 44 ). Considering that virtual education can be implemented at different times and situations such as travel, and since it is much less expensive than face-to-face education due to not being dependent on a specific place and time, therefore this type of education is more extensive than face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…One way to increase the quality of students’ education is to familiarize educators with new educational technologies. The qualitative data suggested that technological support and faculty familiarity with E-learning were substantial influences on students’ satisfaction ( 44 ). Considering that virtual education can be implemented at different times and situations such as travel, and since it is much less expensive than face-to-face education due to not being dependent on a specific place and time, therefore this type of education is more extensive than face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…Como se sabe, a mudança organizacional costuma ser difícil, o que significa que adaptação, flexibilidade e inovação enfrentam enormes desafios institucionais, individuais e coletivos 29,30 . Nesse sentido, embora os resultados apontem uma boa aceitação dos acadêmicos pelo ERE na disciplina de Odontopediatria, mais pesquisas ainda são necessárias para avaliar as fortalezas e limitações dos métodos implementados nas Instituições de Ensino Superior nos cursos de Odontologia durante o período da COVOD-19.…”
Section: Discussionunclassified
“…Advanced teaching equipment was an essential tool for training students who would become medical personnel in the future [ 54 ]. Modern technologies such as multimedia, teaching simulation facilities, and virtual simulation facilities provided students with a virtual “hands-on” experience [ 55 , 56 ], which would stimulate their professional interest and improve their professional satisfaction. Second, the number of study rooms was positively related to student satisfaction [ 57 ].…”
Section: Discussionmentioning
confidence: 99%